MODERN DIAGNOSTIC AND SURGICAL MANAGEMENT OF CRANIOVERTEBRAL JUNCTION INSTABILITY - Sh.T. Arzikulov; R.O. Ismailova; A.I. Ibragimov (Modern American Journals, 2025)
Objective: Craniovertebral junction (CVJ) anomalies with functional instability represent a complex pathology in neurosurgical practice, often leading to spinal cord compression, vascular compromise, and significant neurological deficits. This study aims to improve surgical outcomes by developing a diagnostic algorithm based on neuroimaging criteria to guide the selection of surgical intervention.
Keywords: Craniovertebral junction, CVJ instability, Occipitocervical fusion, Foramen magnum decompression, Goel-Harms technique, Posterior cranial fossa volume.